Low prevalence of MDR‐TB in Lao PDR: results from the first national anti‐tuberculosis drug resistance survey. Issue 4 (31st January 2019) - Iem, Vibol; Dean, Anna; Zignol, Matteo; Vongvichit, Phouvang; Inthavong, Donekham; Siphanthong, Souvimone; Sorsavanh, Theppouthone; Kim, Sang Jae; Shin, Soyoun; Sébert, Jacques; Chittamany, Phonenaly
Abstract: Objective: To present results of the first national anti‐tuberculosis (TB) drug resistance survey conducted in Lao PDR between May 2016 and August 2017 to determine the prevalence of resistance to first‐line anti‐TB drugs among new and previously treated pulmonary TB cases in the country. Methods: Patients with sputum smear‐positive pulmonary TB were enrolled from 42 TB laboratories distributed in 40 clusters throughout the country. Survey sites were selected using probability‐proportional‐to‐size sampling among all diagnostic centres in the country. In addition to smear microscopy, all patients underwent Xpert MTB/RIF testing and those found positive to Mycobacterium tuberculosis underwent sputum culture and drug susceptibility testing using the proportion method on solid Löwenstein–Jensen medium. Results: Among 1006 eligible patients, 946 sputum smear‐positive and Xpert MTB/RIF positive ( Mycobacterium tuberculosis detected) patients were included in the survey, comprising 897 new and 49 previously treated TB cases. The prevalence of rifampicin‐resistant TB was 1.2% (95% CI: 0.5–2.0%, n = 11/897) among new cases and 4.1% (95% CI: 0–9.6%, n = 2/49) among previously treated cases. Among the 946 TB cases confirmed by Xpert MTB/RIF, phenotypic drug sensitivity testing was available for 820 (776 new and 44 previously treated). The prevalence of multidrug‐resistant TB (MDR‐TB) was 0.5% (95% CI: 0–1.0%, n = 4/776) among new cases and 2.3% (95% CI: 0–6.7%, n = 1/44) among previously treated cases. No resistance to second‐line injectable agents nor to fluoroquinolones was detected among MDR‐TB patients. Conclusions: The first national anti‐TB drug resistance survey in Lao PDR demonstrated an encouragingly low prevalence of MDR‐TB. The results appear lower than previous WHO estimates, and in line with the routine surveillance based on Xpert MTB/RIF testing (conducted among 50% of presumptive TB patients in 2017). The country should continue to expand its Xpert MTB/RIF network and strive to achieve universal drug susceptibility testing. Abstract : Objectif: Présenter les résultats de la première surveillance nationale de la résistance aux médicaments antituberculeux, menée en République Démocratique Populaire (RDP) Lao entre mai 2016 et août 2017 afin de déterminer la prévalence de la résistance aux médicaments antituberculeux de première intention chez les nouveaux cas et les cas déjà traités de tuberculose (TB) pulmonaire dans le pays. Méthodes: Les patients atteints de TB pulmonaire à frottis d'expectoration positif ont été recrutés dans 42 laboratoires TB répartis dans 40 groupes à travers tout le pays. Les sites de surveillance ont été sélectionnés sur la base d'un échantillon probabiliste proportionnel à la taille parmi tous les centres de diagnostic du pays. Outre l'examen microscopique des frottis, tous les patients ont subi un test Xpert MTB/RIF et ceux trouvés positifs pour Mycobacterium tuberculosis ont subi une culture d'expectorations et un test de sensibilité aux médicaments en utilisant la méthode des proportions sur un milieu solide de Löwenstein‐Jensen. Résultats: Parmi les 1.006 patients éligibles, 946 patients à frottis positif et Xpert MTB/RIF positif ( Mycobacterium tuberculosis détecté) ont été inclus dans la surveillance, comprenant 897 nouveaux cas et 49 cas de TB déjà traités. La prévalence de la TB résistante à la rifampicine était de 1, 2% (IC95%: 0, 5‐2, 0%, n = 11/897) chez les nouveaux cas et de 4, 1% (IC95%: 0‐9, 6%, n = 2/49) chez les cas traités. Parmi les 946 cas de TB confirmés par Xpert MTB/RIF, des tests de sensibilité phénotypique aux médicaments étaient disponibles pour 820 (776 nouveaux cas et 44 cas traités antérieurement). La prévalence de la TB multirésistante (TB‐MDR) était de 0, 5% (IC95%: 0‐1, 0%, n = 4/776) chez les nouveaux cas et de 2, 3% (IC95%: 0 à 6, 7%, n = 1/44) parmi les cas précédemment traités. Aucune résistance aux agents injectables de deuxième intention ni aux fluoroquinolones n'a été détectée chez les patients atteints de TB‐MDR. Conclusions: La première surveillance nationale de la résistance aux médicaments antituberculeux menée en RDP Lao a révélé une prévalence rassurante de la TB‐MDR. Les résultats apparaissent inférieurs aux estimations précédentes de l'OMS et conformes à la surveillance de routine basée sur le test Xpert MTB/RIF (menée auprès de 50% des patients atteints de TB présumée en 2017). Le pays devrait continuer à élargir son réseau Xpert MTB/RIF et s'efforcer d'atteindre des tests universels de sensibilité aux médicaments.